The Impact of Digital Emotional Intelligence on Constructive Deviance: The Mediating Role of Organizational Learning - Al Issawi , Hasan Ghafil Jawad (Kerbala International Journal of Management and Economics, 2025)
This research aims to study the impact of digital emotional intelligence on constructive deviance among faculty members of the College of Engineering at the University of Information Technology, while testing the mediating role of organizational learning in this relationship. The research relied on the theory of self-control resources and the theory of social cognition to understand the mechanisms of ego depletion and self-efficacy and harness them in the service of the organization by completing tasks and engaging in activities that go beyond the official role, which enhances the organization's ability to work and raises the importance of development and bringing about change. Given the benefits of constructive deviance for the organization through faculty members' behaviors, the importance of the study stems from its aim to fill a knowledge gap related to how to employ digital emotional capabilities to promote positive, atypical behaviors that support institutional development within the higher education environment. The research relied on the descriptive analytical approach, using the questionnaire as a tool to collect data from a random sample of (96) faculty members out of a study population of (127) faculty members in the College of Engineering at the University of Information Technology. The data were analyzed using statistical methods and hypothesis testing. The most important results were the direct effect of digital emotional intelligence on both organizational learning and constructive deviance, the effect of organizational learning on constructive deviance, and its mediating role in the relationship between digital emotional intelligence and constructive deviance , The constructive approach reflects a knowledge and cultural gap that limits the College of Engineering's ability to promote administrative and academic innovation, develop the digital learning environment, and support strategies for effective digital transformation.